Atomic spectrometry update: review of advances in the analysis of metals, chemicals and materials. Issue 11 (26th October 2021) - Carter, Simon; Clough, Robert; Fisher, Andy; Gibson, Bridget; Russell, Ben
Abstract : This review covers advances in the analysis of advanced materials, metals, fuels and lubricants, nanostructures, ceramics, refractories, organic and inorganic chemicals, catalysts and nuclear materials by a range of techniques including X-ray, ICP, LIBS, mass spectrometry, synchrotron-based techniques, plus non-destructive and ablation surface techniques. Abstract : This update covers the literature published between June 2020 and May 2021 and is the latest part of a series of annual reviews. It is designed to provide the reader with an overview of the current state of the art with respect to the atomic spectrometric analysis of various metals, chemicals and materials. It is not designed to be a comprehensive review of all papers that have used an atomic spectrometric technique. Instead, it includes only those papers that have some novelty through making an advance in either knowledge or the application of atomic spectrometry. Also included, especially for forensic-based applications, for recycling applications and for cultural heritage samples, are those papers that have treated the analytical data produced with chemometric packages to provide invaluable information on provenance or to aid identification. Other research has focussed on calibration strategies for LIBS analyses and improving the resolution of depth and lateral profiling to facilitate the elucidation of mechanistic aspects of electronic components. An additional topic of interest includes the identification of oxidation states and neighbouring atoms using techniques such as XPS and XANES, again attempting to elucidate mechanisms for electronic components or to elicit speciation data.